Catview eine kritische Lektüre von David Hockneys "Mr and Mrs Clark and Percy" (1971) als interspecies-Begegnung im Wohnen - Keim, Christiane (2023)
300 David Hockney’s painting Mr and Mrs Clark and Percy from 1971 is part of a series of depictions of the domestic produced by the British artist during the 1960s and 1970s. It is the only image within this group of portraits of Hockney’s relatives and friends that, along with the human figures, the interior, and various domestic objects, includes a non-human resident: a cat, identified in the title by the name Percy. Numerous analyses of this very well-known Hockney work either fail to mention the pet animal completely or refer to it only in passing. Given the very prominent po- sitioning of Percy in the picture, this disregard seems astounding, and in my view it is a symptom, a symptomatic over-sight deriving from the concept of anthropological difference, the binary-hierarchical opposition between human and animal that pervades scholarly discourse, including the discourse around dwelling. This paper fosters a reading of this image that is focused on the critique of anthropocentric viewpoints. Two guid- ing texts in this context are Jacques Derrida’s The Animal That Therefore I Am (2010), in which Derrida proceeds from a domestic scene involving eye contact with his cat in his apartment to a revision of thinking and speaking about animals, and Roland Barthes’ lecture series How to Live Together (1977/2007), in which Barthes reflects on types of living and dwelling in communities, including in animal societies.
Keywords: Hockney, David -- 1937-; Katze -- Motiv; Malerei